A survey of favorable online E-sport game activities during the Covid-19 pandemic - Admaja, A. T.; Saputro, J. A. (International Journal of Contemporary Research and Review, 2021)
The positive and negative impacts or pros and cons in the COVID-19 pandemic can be a blessing or a disaster depending on the perspective of the mind. Researchers try to examine the development of e-sports which is now starting to become popular and even an addiction for all ages from children to adults, and is supported by many athletes who have achieved world-class achievements in FIFA or Pro Evolution Soccer, PUBG, and other online games. The problem from the research is the basis why researchers are interested in researching by using a survey method to the point of view of students and the point of view of parents and the point of view of teachers / lecturers about the development of e-sports which is very popular today. This research data is on a regional scale such as the province of Yogyakarta and if possible will be distributed via google form to all corners of the country so that the data obtained is more diverse according to the point of view of each region according to the culture and circumstances of each region. Based on the description above, it can be concluded E-Sports itself is actually video game competitions between players who have made gaming their real profession. E-Sports is also known as competitive gaming or pro gaming. input from players and teams as well as output from the E-Sports system mediated by the human-computer interface. Most commonly, E-Sports takes the form of organized, multiplayer video game competitions, primarily between (but not limited to) professional players. Tournaments such as The International, League of Legends World Championship, Battle.net World Championship Series, Evolution Championship Series, Intel Extreme Masters, and Smite World Championship provide both live-streamed competition and prize money and salaries for a fantastic number of competitors. Some people think that gaming is no longer a reliever of fatigue when there is a lot of boredom at work or studying at school but as a profession that can be guaranteed income and can be capital in life. Online gaming athletes start training with their gadgets or joysticks every day in order to achieve the champions they desire. Call it games that are widely played in all circles, young and old, namely Pro Evolution Soccer (PES) and FIFA, mobile legends, PUBG, Free Fire, DOTA, COC, and many other online games that are now very popular